A survey on development of energy service industry in Zhejiang China - Qu, Yan; Wang, Xu Yan; Darkwa, Jo (Trans Tech Publications, 2014)
Energy service industry (ESI) has grown quickly recent year in China. A main and important role in ESI is Energy Service Company (ESCO) which engages in reducing energy consumption through retrofitting the existing facilities. This survey focuses on the development of energy service industry in Zhejiang involving opportunities and barriers of the growth of ESCO. The results show that generating a third-party finanicing network, building more perfect policies and regulations and raising credit awareness are significant factors for healthy development of ESI.